Da imagem nascente à imagem consagrada : a construção da imagem do gaúcho pelos pincéis de Cesáreo Bernaldo de Quirós, Pedro Figari e Pedro Weingärtner - Oliveira, Luciana da Costa de (2017)
The main objective of this doctoral thesis is to analyze the way in which the image of the gaucho and the gaúcho was constructed and consecrated in the Argentine, Uruguayan and Brazilian painting of the 20th century, especially in the painting by Cesáreo Bernaldo de Quirós (1879-1968), Pedro Figari (1861-1938) and Pedro Weingärtner (1853-1929). In this perspective, starting from theoretical-methodological issues that include not only the dialogues that the images interlock, but, especially, their temporal and mnemic links, it was also aimed to establish a relation between the work that celebrated the gaucho and the gaúcho in the twentieth century with those that preceded it. Thus combining the nascent image of the eighteenth and nineteenth centuries with that which was consecrated in the twentieth century, it was intended to define the diverse and multiple threads that, intertwined, produced a wide and complex network of meanings around the image of the gaucho and the gaúcho. These same threads, woven by times and memories, by yearnings and desires, besides particularizing the image of the man from the pampa, also reveals their uses and their functions.